1) 4K+O2=2K2O
K2O+H2O=2KOH
2KOH+H2SO4=K2SO4+2H2O
2K(+)+2OH(-)+2H(+)+SO4(2-)=2K(+)+SO4(2-)+2H2O
2H(+)+2OH(-)=2H2O
2) S+O2=SO2
SO2+H2O=H2SO3
H2SO3+2NaOH=Na2SO3+2H2O
2H(+)+SO3(2-)+2Na(+)+2OH(-)=2Na(+)+SO3(2-)+2H2O
3) 4Al+3O2=2Al2O3
Al2O3+6HCl=2AlCl3+3H2O
AlCl3+3NaOH=Al(OH)3+3NaCl
Al(+3)+3Cl(-)+3Na(+)+3OH(-)=Al(OH)3+3Na(+)+3Cl(-)
Al(+3)+3OH(-)=Al(OH)3
1) 4K+O2=2K2O
K2O+H2O=2KOH
2KOH+H2SO4=K2SO4+2H2O
2K(+)+2OH(-)+2H(+)+SO4(2-)=2K(+)+SO4(2-)+2H2O
2H(+)+2OH(-)=2H2O
2) S+O2=SO2
SO2+H2O=H2SO3
H2SO3+2NaOH=Na2SO3+2H2O
2H(+)+SO3(2-)+2Na(+)+2OH(-)=2Na(+)+SO3(2-)+2H2O
2H(+)+2OH(-)=2H2O
3) 4Al+3O2=2Al2O3
Al2O3+6HCl=2AlCl3+3H2O
AlCl3+3NaOH=Al(OH)3+3NaCl
Al(+3)+3Cl(-)+3Na(+)+3OH(-)=Al(OH)3+3Na(+)+3Cl(-)
Al(+3)+3OH(-)=Al(OH)3